Development of laser-induced fluorescence to quantify in-cylinder fuel wall films. (January 2018) - Geiler, Jan N; Grzeszik, Roman; Quaing, Sebastian; Manz, Andreas; Kaiser, Sebastian A
Laser-induced fluorescence of a fuel tracer is a very sensitive technique to image in-cylinder liquid fuel films, but quantification of the measured film thickness has proven difficult so far. This article describes improvements in the quantification procedure and presents an example application in a motored, optically accessible spark-ignition engine with direct injection. We designed a calibration tool that could be pressurized and heated, allowing investigation of the laser-induced fluorescence intensities at temperatures exceeding the liquid's standard-pressure boiling point. The fluorescence intensity of liquid toluene and 3-Pentanone dissolved in isooctane upon excitation with a pulsed laser at 266 nm was investigated as a function of temperature and pressure. Consistent with the literature results on gas-phase laser-induced fluorescence, the signal from toluene was much stronger than from 3-Pentanone, about two orders of magnitude for films thinner than 50 μm. Laser-induced fluorescence from both tracers decreased with increasing temperature but that of toluene significantly more. The response to pressure was less pronounced. For imaging across a large field of view, the spatial non-uniformity of laser excitation and detection efficiency was taken into account using a solid fluorescing substrate, an inexpensive Schott-glass WG280 filter. Isooctane with 0.5 vol.% toluene was used for application in the motored engine, imaging the liquid film on the piston-top window after direct injection from a central multi-hole injector. Air as a bulk gas was found to be advantageous over nitrogen in that gas-phase fluorescence was quenched by oxygen. The imaged film distributions and thicknesses and the derived total fuel film mass were physically plausible. Consistent with the recent literature results from a constant pressure vessel, increasing injection pressure from 50 to 100 bar did not decrease wall wetting but further increase to 200 bar did.